2018
DOI: 10.1097/ajp.0000000000000579
|View full text |Cite
|
Sign up to set email alerts
|

Does Self-compassion Benefit Couples Coping With Vulvodynia? Associations With Psychological, Sexual, and Relationship Adjustment

Abstract: Findings suggest that self-compassion is a promising protective factor in the experience of vulvodynia and associated distress. Interventions aimed at increasing self-compassion could enhance the efficacy of psychological treatments for these women and their partners. Further studies are needed to better understand the correlates of self-compassion among this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…While there are several studies of psychosocial factors in Vulvodynia (Chisari & Chilcot, 2017; Santerre‐Baillargeon et al., 2018), and its impactful nature is significantly associated with psychological, emotional and sexual difficulties (Bois et al., 2016; Gates & Galask, 2001; Khandker et al., 2011), there is no coherent understanding of how psychosocial factors impact on outcomes or interact with relevant disease variables.…”
Section: Introductionmentioning
confidence: 99%
“…While there are several studies of psychosocial factors in Vulvodynia (Chisari & Chilcot, 2017; Santerre‐Baillargeon et al., 2018), and its impactful nature is significantly associated with psychological, emotional and sexual difficulties (Bois et al., 2016; Gates & Galask, 2001; Khandker et al., 2011), there is no coherent understanding of how psychosocial factors impact on outcomes or interact with relevant disease variables.…”
Section: Introductionmentioning
confidence: 99%
“…Eight articles were further excluded, for reasons shown in the Appendix section ( Figure 1). Finally, 19 articles (n=2,713 patients, of which 73.3% were females) met our eligibility criteria and were included in this systematic review [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The baseline characteristics of the included studies are comprehensively described in Table 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…All included studies evaluated the correlation of self-compassion with other important psychosocial outcomes such as depression, anxiety, stress, resilience, shame, quality of life, and other outcomes as shown in Table 2. Nine studies evaluated the correlation between self-compassion and depression [16,18,[20][21][22][23]26,29,33]. All studies found that a higher self-compassion was correlated with lower levels of depression in individuals with a medical illness.…”
Section: Important Correlationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cancer patients, self‐compassion was shown to promote adaptive rather than maladaptive coping, 26 and was significantly associated with lower stress and better quality of life 27 . Santerre‐Baillargeon, Rosen 28 found increased self‐compassion to be associated with a significant decrease in sexual distress for the male partners of women with vulvodynia (a condition of sexual pain) yet did not have a significant effect for the women experiencing the pain.…”
Section: Introductionmentioning
confidence: 99%